Multidisciplinary analysis of subsonic stealth unmanned combat aerial vehicles - Sepulveda, Eduardo; Smith, Howard; Sziroczak, David (Springer, 2018)
In this paper, the GENUS multidisciplinary aircraft design and analysis environment is presented in its application to the conceptual design of tailless, low-observable unmanned combat aerial vehicles (UCAVs). Analysis disciplines comprise a variety of low to medium fidelity, physics-based and empirical methodologies, as well as higher order panel method aerodynamic analysis. Stealth considerations have been included in terms of a radar cross section analysis through a physical optics approximation method, with results verified against a well-known radar cross section prediction code. Preliminary results show good agreement for gross and empty masses when compared to several existing UCAV demonstrators and conceptual designs. A further validation of the presented methodologies is evaluated through the design, analysis, and optimisation of an unmanned strike fighter concept.
Keywords: UCAV; Stealth; Conceptual design; Tailless aircraft; UAV